Perancangan Sistem Manajemen Dropship Berbasis Web untuk PT Xarana Djaya Motor - Theresia Gabriella; Bhustomy Hakim (LPPM STIKI MALANG, 2025)
Indonesia’s online retail is expanding alongside the national digital economy: 56.1% of global internet users shop on weekends, with Indonesia ranking ninth at 59.3%. The digital economy is projected to reach IDR 5,800 trillion by 2030 (USD 360 billion), and in 2023 Indonesia accounted for 40% of ASEAN’s e-commerce market. In this context, PT Xarana Djaya Motor, a multi-brand motorcycle spare-parts distributor, runs a dropshipping model with multiple online sellers. Yet orders and shipment confirmations are still coordinated via chat and reentered manually, causing duplicate entries, processing delays, and limited real-time stock visibility. This study designs and implements a web-based Dropship Management Application that centralizes catalog, order, shipment, and return workflows. Analysis uses UML/ERD; implementation employs Laravel (PHP) and MySQL. Alpha/black-box testing validates key rules (one shipment per order) with multiple items and partial returns at the order-item level. Results indicate reduced manual handling, improved data accuracy, and clearer status visibility as supported by centralized workflows and functional (black-box) acceptance tests. The work contributes a reusable reference architecture for SMEs, with future extensions to marketplace API integration, automated label generation, analytics dashboards, and mobile access.